1988
DOI: 10.1007/bf01406615
|View full text |Cite
|
Sign up to set email alerts
|

An adoptive immunotherapy of patients with medulloblastoma by lymphokine-activated killer cells (LAK)

Abstract: An adoptive immunotherapy of 6 patients with medulloblastoma by lymphokine-activated killer (LAK) cells is described. They were from 2 to 9 years in age and had cerebrospinal fluid (CSF) dissemination of the tumours. All patients underwent the whole-neuraxis irradiation and chemotherapy. After the usual treatments, they were submitted to an adoptive transfer of one-haplotype identical LAK cells. The LAK cells were induced from peripheral blood lymphocytes (PBL) of their relatives with human recombinant interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore, treatment-related toxicities, such as irreversible neurological adverse effects, constitute a primary limitation of conventional treatment. Preliminary clinical observation suggests that MB might regress via its recognition by immune effector cells such as natural killer (NK) cells [3][4][5][6]. NK cells are large granular lymphocytes of the innate immune system.…”
Section: Medulloblastoma and Nk Cell Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, treatment-related toxicities, such as irreversible neurological adverse effects, constitute a primary limitation of conventional treatment. Preliminary clinical observation suggests that MB might regress via its recognition by immune effector cells such as natural killer (NK) cells [3][4][5][6]. NK cells are large granular lymphocytes of the innate immune system.…”
Section: Medulloblastoma and Nk Cell Susceptibilitymentioning
confidence: 99%
“…However, Shimizu et al and Okamoto et al published their experience with intrathecally administered LAK cells, observing complete response in three of eight patients with MB [4,34]. Silvani et al also reported a case regarding intrathecally administered LAK cells with MB remission maintained for more than 30 months [3].…”
Section: Clinical Datamentioning
confidence: 99%
“…Retreatment of medulloblastomas with whole-brain irradiation and misonidazole was once performed, but the results showed high radiation toxicity with efficacy that was no better than the results attained in patients receiving salvage chemotherapy [15]. A few innovative approaches have been or are being proposed for treating medulloblastomas with CSF dissemination including the following: adoptive immunotherapy using lymphokine-activated killer cells [16], the ventriculolumbar perfusion of ACNU [17] and intrathecal injection of reovirus [18.] So far, only a few successful cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades of the twentieth century application of lymphokine actived killer (LAK) cells directly administered intrathecally with co-administration of human recombinant IL-2 for patients with recurrent disseminated medulloblastoma was published. Some of the limited number of patients showed long term survival (Okamoto et al, 1988;Silvani et al, 1994). Another method is the adoptive transfer of tumor-specific cytolytic T cells to the tumor bed and cerebrospinal fluid.…”
Section: Targeted Treatmentmentioning
confidence: 99%